Loan loss provisions and pro-cyclicality: the case of Commonwealth of Independent States (CIS). - Mussabekova, Raushan (2011)
In the light of the recent global crisis the disputes related to the pro-cyclicality of banks’ loan loss provisioning behaviour became one of the widely discussed topics in existing research. The core idea of the problem states that banks create fewer provisions during good times while during bad times provisioning level significantly increases which leads to the decline of lending in the economy at the same time as the country desperately needs credit from the banks. Previous empirical research documented cases of pro-cyclical bank provisioning behaviour. In this research loan loss provisions of CIS banks have been examined for the presence of pro-cyclicality. Following the outcomes of existing research we have tested three hypotheses: the pro-cyclicality hypothesis, income smoothing and capital management hypotheses. Based on the sample of 64 commercial banks from Kazakhstan, Russia and Ukraine which have the most advanced banking systems among CIS countries the results indicate confirmation of pro-cyclical loan loss provisioning behaviour. However our empirical results have revealed signs of counter-cyclicality in provisioning systems of CIS banks, because the Russian regulation for standard loans from homogenous group and Ukraine for all standard loans obliges banks to create general loan loss provisions. However we have not documented income smoothing among CIS banks and test results have shown that loan loss provision changes fail to relate to the changes of earnings before taxes and provisions. Capital management hypothesis has been confirmed meaning that CIS banks use loan loss provisions for improvement of their capital ratios.